The dead fathers club - Haig, Matt, 1975- (Viking, 2006)
Eleven-year-old Philip Noble has a big problem. It all begins when his dad appears as a ghost at his own funeral and introduces Philip to the Dead Fathers Club. Philip learns the truth about ghosts: the only people who end up as ghosts have been murdered. So begins Philip's quest to avenge his dad.